UJI FARMAKOLOGI SEDIAAN PLESTER PATCH DARI LIMBAH KULIT PISANG KEPOK (MUSA ACUMINATA) UNTUK PENYEMBUHAN LUKA BAKAR - Syamsuri Syakri (Jurnal Kesehatan, 2019)
Telah dilakukan penelitian mengenai Uji Farmakologi Sediaan Patch Dari Limbah Kulit Pisang Kepok Untuk Penyembuhan Luka Bakar. Tujuan penelitain ini untuk melakukan uji efektivitas dengan menggunakan hewan coba kelinci, serta pembuatan plester patch untuk memberikan suatu kenyamanan dan kemudahan kepada konsumen dalam mengobati luka. Peneltian ini menggunakan metode kuantitatif dengan cara metode eksperimental laboratorium, cara kerjanya berupa pengambilan sampel, ektraksi kulit buah pisang kepok, membuat plester patch dari 3 macam formula kemudian membandingkan dengan kontrol positif dan negatif, evaluasi plester patch¸dan setelah pengujian daya sembuh luka pada hewan kelinci. Dari hasil penelitian didapatkan Formula III yang memiliki efektifitas paling baik dalam menyembuhkan luka yaitu konsentrasi 30% kulit buah pisang kepok. ABSTRACTResearch has been conducted on the Pharmacological Test of Patches Preparation from Kepok Banana Skin Waste to Heal Burns. The use of immature kepok banana peels to help speed up the duration of wound healing has already been done, but in previous studies, kepok banana peel was extracted, but made in gel form, whereas in patch plaster preparations had never been studied before. The purpose of this research is to make patch plaster preparations that have the best effectiveness in healing wounds, as well as making patch plasters to provide comfort and convenience to consumers in treating wounds. This research uses a quantitative method by means of laboratory experimental methods, how it works in the form of sampling, extraction of kepok banana peel, making patch plaster using active ingredients kepok banana peel extract (Musa acuminate), and other additives in the form of glycerin, chitosan, HPMC, Tween 80, then formulated into 3 types of formulas, then compared with positive and negative controls, evaluation of patch patches and after testing the healing power of wounds in rabbit animals. From the results of the study it was found that Formula III had the best effectiveness in healing wounds, namely the concentration of 30% kepok banana peels.